2023
DOI: 10.1038/s41598-023-27600-9
|View full text |Cite
|
Sign up to set email alerts
|

Second law assessment of di methyl ether and its mixtures in domestic refrigeration system

Abstract: Dimethyl ether (DME) and its blend of refrigerants (R429A, R435A, and R510A) are considered in this study's second law analysis as potential replacements for R134a. The performance of various refrigerants in a vapour compression refrigeration system is examined using the Design package CYCLE D. The software REFPROP 9.0 is used to extract all of the thermal and physical parameters of DME and its blend of refrigerants. The Second law performance parameters such as Efficiency Defects, Entropy generation and Exerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…Theoretical study by Baskaran et al [7] showed that DME refrigerant has advantages compared to R152a in replacing R134a. Thermodynamic studies on DME mixed refrigerants (R429A, R435A, and R 510A) also show an increase in the coefficient of performance (COP) and exergy efficiency compared to R134a refrigerant [8].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical study by Baskaran et al [7] showed that DME refrigerant has advantages compared to R152a in replacing R134a. Thermodynamic studies on DME mixed refrigerants (R429A, R435A, and R 510A) also show an increase in the coefficient of performance (COP) and exergy efficiency compared to R134a refrigerant [8].…”
Section: Introductionmentioning
confidence: 99%
“…All nanolubricants based on TiO 2 have been observed to reduce average power consumption. Baskaran et al [16][17][18][19][20][21][22][23][24][25][26][27] evaluated the performance of a vapour compression refrigeration device using a variety of different refrigerants (including refrigerant mixtures) and nanorefrigerants, and their findings were compared to those obtained by using R134a as a potential alternative replacement. An investigative test rig is indigenously created and manufactured to conduct the examinations.…”
Section: Introductionmentioning
confidence: 99%
“…DME merupakan salah satu senyawa hidrokarbon yang ramah lingkungan dengan nilai ODP sebesar nol dan nilai GWP yang sangat kecil. DME memiliki sifat yang mirip denggan R134a sehingga dapat menjadi refrigeran alternatif pengganti R134a (Baskaran, Manikandan, & Sureshkumar, 2018).…”
unclassified